2003
DOI: 10.1038/sj.ejcn.1601632
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in urinary and household salt iodine content among pregnant and lactating women of the plains of Nepal

Abstract: Objective: To determine the extent and causes of iodine deficiency among women during pregnancy and lactation in the southeastern plains of Nepal. Design, Setting and Subjects: Urinary iodine (UI) was assessed as an indicator of iodine status in spot urine samples of women participating in a field trial in three rural communities in the plains of southeastern Nepal. Samples were collected during pregnancy (n ¼ 1021) and during lactation at 3-4 months postpartum (n ¼ 1028) at a central clinic; 613 women were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
(32 reference statements)
5
24
1
2
Order By: Relevance
“…Inhomogeneity is not therefore rare; the large inhomogeneity found in some samples is worrisome. Although a similar study has not been conducted in the United States, an extensive study in Nepal showed that as salt iodine content varies as a function of season (decreasing in more humid weather), a similar variation in UI is observed (88) suggesting that salt is an important source of iodine. If salt does supply a significant portion of the iodine intake of a pregnant/lactating woman in the United States (note that a large fraction of preor postnatal vitamins contain no iodine) and she is unfortunate enough to pick a can of salt that is low in iodine or in which iodine distribution is greatly inhomogeneous, there is potential for serious harm.…”
Section: Iodine In Freshly Opened Containers Of Us Iodized Saltmentioning
confidence: 96%
“…Inhomogeneity is not therefore rare; the large inhomogeneity found in some samples is worrisome. Although a similar study has not been conducted in the United States, an extensive study in Nepal showed that as salt iodine content varies as a function of season (decreasing in more humid weather), a similar variation in UI is observed (88) suggesting that salt is an important source of iodine. If salt does supply a significant portion of the iodine intake of a pregnant/lactating woman in the United States (note that a large fraction of preor postnatal vitamins contain no iodine) and she is unfortunate enough to pick a can of salt that is low in iodine or in which iodine distribution is greatly inhomogeneous, there is potential for serious harm.…”
Section: Iodine In Freshly Opened Containers Of Us Iodized Saltmentioning
confidence: 96%
“…Pregnant women require 250 μg intake of iodine per day, and UIC is a good indicator of recent iodine intake. 2,13 The median UIC among pregnant women in the present study was 282.2 μg/L, which indicates more than adequate iodine intake among pregnant women of eastern Nepal. However, 17 (18.5%) women had UIC<150 μg/L, which indicates insufficient iodine intake in those women recently.…”
Section: Discussionmentioning
confidence: 92%
“…The other determinant of UIC was breast-feeding, where breast-feeding women had a significantly lower UIC than women who were not breast-feeding. Reduced UIC during breast-feeding has been found in other studies (30)(31)(32) and is probably a reflection of the iodine excretion in breast milk (33) .…”
Section: Urinary Iodine Concentrationmentioning
confidence: 86%